The Role of Internal Auditing Practices on the Performance of Local Government: A Case of Central Division Kisoro Municipality. - Ngabire, Nobert (Kabale University, 2023)
The purpose of the study was to establish the role of auditing practices in the performance of local government with specific reference to Central Division Kisoro Municipality. The study was guided by the following specific objectives; to find out the nature of the internal audit in Central Division Kisoro Municipality, to identify the challenges faced by the internal audit in enhancing financial performance in Central Division Kisoro Municipality, and to identify solutions to he challenges faced by internal audit in Central Division Kisoro Municipality. The study population comprised about 100 people. The researcher used 50 respondents who Were selected from Central Division, Kisoro Municipality. In this study, 60 respondents were chosen qualitatively and quantitatively where all the respondents were interviewed, and others were given questionnaires. This Research study employed descriptive research where both Primary and Secondary data were collected. The study also used cross-sectional surveys that involved different ages, gender status, and educational background among the selected respondents. The researcher used purposive sampling as it was the one that was convenient. However, the researcher also used systematic sampling as it helped her come up with firsthand information from respondents. The research tools that were used to collect data include Questionnaires, interviews group discussions targeting the following recipients, key informants, and focused groups, and these were used to obtain both qualitative and quantitative data. The study established that Central Division Kisoro Municipality, audit department is responsible for making comparisons between different period's figures with the current period figures and finding out the changes which at the time must be explained and justified. Findings from the study further revealed that internal audit in the local government of Central Division Kisoro Municipality make comparisons of physical items and if possible sometimes count them in the trial balance of the current year with items of that trial balance of the previous year and see whether an item has been left out which at times are traced to the ledger to find exactly that which has been left out. The study also concluded that political interference, corruption, conflict of interest, inadequate skills, inadequate information, inadequate funds, and improper communication flow are the major challenges faced by internal audit and financial performance of Central Division Kisoro Municipality. The study recommended that the employment of a strong internal control system in local governments will eventually reduce the frauds and errors done by the employees.